André Bruyère et la synthèse des arts : projet de Village polychrome avec Fernand Léger (1953) - Thomas Gluckin (In Situ)
In 1951, the Groupe Espace was formed by André Bloc (1896-1966), sculptor and editor of L’Architecture d’aujourd’hui and Art d’aujourd’hui. The group sought to unite creators around a common ambition of achieving a synthesis of the arts in order to overcome the traditional division between painting, sculpture and architecture. In this context, in 1952 and 1953, two members of the group and longtime friends of André Bloc, the architect André Bruyère (1912-1998) and the painter Fernand Léger (1881-1955) were commissioned by a Brazilian media magnate, Francisco Assis de Chateaubriand (1892-1968), to design a housing-project called Village polychrome, a polychrome village to be located near Biot (Alpes-Maritimes). The project was intended to be a resort and a village for artists. According to Bruyère’s wish, it created living space in a decor by Fernand Léger, integrated into the landscape. Although it was not carried out, the project is a significant one for the 1950s in terms of its attempt to express an alternative to the hegemony of modernist architecture through the question of the synthesis of the arts, an alternative involving a new conception of a locally defined space using the free forms. Thus, the housing and the living environment play a major role in the project and reflect the attachment of both figures to the relations between the individual, the work and the environment. First, the project itself will be studied through the drawings of Bruyère coloured by Léger. Subsequently the study will be put into perspective with some research on other members of the Groupe Espace, especially André Bloc and his Sculptures-habitacles (sculpture-compartments). Finally, the study will show how a collective episode around the synthesis of the arts and the quest for some hedonism launched the innovative reflections of Bruyère on living space with a topological and phenomenological character in the 1960s and 1970s.